2020
DOI: 10.56093/ijas.v90i10.107885
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of tillage, crop residue mulch and nitrogen interactions on yield and water use efficiency of wheat (Triticum aestivum) using DSSAT model

Abstract: Field experiment was conducted during rabi season for two years (2014-15 and 2015-16) on wheat cultivar HD- 2967 in a sandy loam soil (Inceptisol) for simulation of evapotranspiration, crop water use efficiency (WUE) and yield of wheat under different tillage (Conventional tillage (CT) and no tillage (NT)), residue (maize residue @ 5 t ha-1 (R+) and without residue (R0)) and nitrogen (60, 120 and 180 kg N ha-1, representing 50% (N60), 100% (N120) and 150% (N180) of the recommended dose of nitrogen for wheat (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Pradhan et al . (2011) explained that greater Olsen P contents in ZT were due to the formation of stable complexes of P-fixing/immobilising ions like Ca 2+ , Fe 3+ and Al 3+ with SOM. Consistent with the results of Yadvinder-Singh et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pradhan et al . (2011) explained that greater Olsen P contents in ZT were due to the formation of stable complexes of P-fixing/immobilising ions like Ca 2+ , Fe 3+ and Al 3+ with SOM. Consistent with the results of Yadvinder-Singh et al .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed greater P availability in the surface soil layers under ZT with residue retention as compared to CT (Dıaz-Zorita and Grove 2002; Kumar et al 2004). Pradhan et al (2011) explained that greater Olsen P contents in ZT were due to the formation of stable complexes of P-fixing/immobilising ions like Ca 2+ , Fe 3+ and Al 3+ with SOM. Consistent with the results of Yadvinder- Singh et al (2004), increase in available K in soil continuously amended with rice residue was relatively small.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…Economic, social, political, technological, and human hazards all have an impact on the agriculture industry, which has a very sensitive and unique structure. Some variables may be taken into account for efficient production (Rani et al 2020). From this perspective, agriculture's effective performance in terms of human nutrition is inextricably linked to the management of hazards that endanger agricultural productivity (Tümer et al 2010).…”
Section: Introductionmentioning
confidence: 99%